Improving Repurchase Intention on Green Marketing Strategy - Ni Wayan Eka Mitariani; Agus Wahyudi Salasa Gama; I Gusti Ayu Imbayani (Jurnal Organisasi dan Manajemen, 2022)
Purpose – The best eco-friendly brands are rapidly gaining a powerful reputation for their commitment to the environment. Organisations of all sizes are discovering that the present consumers need more than just the right products and services. Therefore, this study aims to analyze the effect of green brand image on the repurchase intention mediated by brand trust and attachment. Methodology – The samples were cosmetic products and herbal oil users, which applied green products in Bali, Indonesia. In this asaay, data were obtained by distributing questionnaires to 149 respondents, with the PLS model used to analyze the hypothetical results acquired. Findings – The results showed that brand image positively affected trust, attachment, and repurchase intention. The effect of this image on repurchase intention was also mediated by green trust. Based on the findings, the investment of resources helped increase trust, attachment, and repurchase intention, to enhance brand image. Originality – This study developed a strategical marketing framework, to increase the repurchase intention of green products. According to the analytical novelty, brand image indirectly affected repurchase intention through trust. This strategy encouraged customers to always perform repeated purchases from trustable companies producing environmentally friendly green products and services.